LEGAL PROTECTION FOR USERS OF PEER-TO-PEER LENDING SERVICES IN THE FINTECH ECOSYSTEM IN INDONESIA - Amanda Lanisya; Indah Kusuma Wardhani (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
The evolution of financial technology (fintech) has spurred numerous innovations in digital financial services, notably Peer-to-Peer (P2P) Lending platforms. These platforms facilitate straightforward funding access for individuals by linking lenders and borrowers via online interfaces. Yet, P2P lending expansion has engendered several legal issues, including the proliferation of unlicensed fintech entities, improper handling of personal information, and collection methods contravening statutory norms. This investigation examines the regulatory framework for P2P lending in Indonesia, the nature of safeguards for platform users, and the obstacles alongside strategies for enhancing protections within the fintech landscape. Employing normative legal inquiry with statute-based and conceptual methodologies, the findings indicate that P2P lending governance in Indonesia draws from diverse instruments, encompassing the Financial Services Authority statute, Financial Services Authority rules on IT-enabled crowdfunding, and provisions for consumer rights and data privacy. User protections in fintech are delivered via preemptive and corrective measures. Nevertheless, enforcement encounters persistent hurdles, underscoring the imperative for regulatory fortification, intensified oversight, and elevated public financial awareness.